Hepatitis E Infection in Solid Organ Transplant Recipients in Turkey - Öğüt, Seval; Sayıner, Ayça Arzu; Otlu, Barış; Bozdayı, Gülendam; Zeytinoğlu, Ayşın; Aksaray, Sebahat; Çolak, Dilek; Gökahmetoğlu, Selma; Aysın, Murat (Turkish Journal of Gastroenterology, 2022)
Background: Hepatitis E virus is a re-emerging pathogen with an increase in human cases that can lead to chronic infection in immunosuppressed patients. Turkey is located between Asia and Europe, 2 regions with distinct epidemiological and clinical features of hepatitis E virus infection. This multicenter cross-sectional study aimed to investigate the prevalence of hepatitis E virus infection in liver and kidney transplant recipients in Turkey and to determine the role of possible transmission factors. Methods: A total of 485 plasma samples of solid organ recipients were collected from 7 transplantation centers in Turkey. Samples were tested for anti-hepatitis E virus immunoglobin M, immunoglobin G, and hepatitis E virus ribonucleic acid. Water- and food-related risk factors were evaluated by a questionnaire. Results: Samples of 300 kidney and 185 liver recipients were collected. Hepatitis E virus ribonucleic acid was tested in 472 samples and none were positive. Anti-hepatitis E virus immunoglobin G and immunoglobin M were detected in 84 (17.3%) and 3 (0.6%) patients, respectively. Seropositivity was associated with older age, male gender, being a liver recipient, and being infected with hepatitis B virus and/or hepatitis C virus. None of the patients under the age of 30 were seropositive. Hepatitis E virus immunoglobin G prevalence was higher in the Central East and Southeast Anatolia. Eating raw meat was the only independent variable associated with hepatitis E virus seropositivity. Conclusion: This is the first prevalence study of hepatitis E virus infection in solid organ recipients in Turkey. Anti-hepatitis E virus immunoglobin G prevalence was 17.3% which was higher than the previously reported rate in blood donors. Seropositivity was significantly higher in liver recipients. Despite the high antibody prevalence, none of the patients were viremic.